2017
DOI: 10.1109/tnb.2017.2757906
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Modeling and Analysis of Intrabody Terahertz Nanoscale Communication

Abstract: Wireless communication among implanted nano-biosensors will enable transformative smart health monitoring and diagnosis systems. The state of the art of nano-electronics and nano-photonics points to the terahertz (THz) band (0.1-10 THz) and optical frequency bands (infrared, 30-400 THz, and visible, 400-750 THz) as the frequency range for communication among nano-biosensors. Recently, several propagation models have been developed to study and assess the feasibility of intra-body electromagnetic (EM) nanoscale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…In particular, the authors in [196] presented an attenuation model of intrabody THz propagation to facilitate the accurate design and practical deployment of iWNSNs. In subsequent studies, the authors also demonstrated both the photothermal impact [197] along with the noise effect [198] of THz intrabody communication to further verify the feasibility and prosperity of such propagation mechanism.…”
Section: A Terahertz Nanoscale Applicationsmentioning
confidence: 87%
“…In particular, the authors in [196] presented an attenuation model of intrabody THz propagation to facilitate the accurate design and practical deployment of iWNSNs. In subsequent studies, the authors also demonstrated both the photothermal impact [197] along with the noise effect [198] of THz intrabody communication to further verify the feasibility and prosperity of such propagation mechanism.…”
Section: A Terahertz Nanoscale Applicationsmentioning
confidence: 87%
“…MNC is a bio-inspired approach as it is inspired by the natural phenomenon of biology and deals with the emission, propagation, and reception of molecules using Nanomachines (natural/artificial) [2]. EMNC is inspired by miniaturization of communication devices and deals with transmission propagation and reception of EM waves radiated by some novel nanodevice in the Terahertz band [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…In other applications, external EM radiation is used to heat the medium or influence a process. In such scenarios, an increase in temperature due to the absorption of EM energy by molecules results in radiation absorption noise in MNC [4]- [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations